Switching of Giant Lateral Force on Sub‐10 nm Particle Using Phase‐Change Nanoantenna. Issue 2 (5th February 2018) - Cao, Tun; Bao, Jiaxin; Mao, Libang
Abstract: We numerically show that a giant lateral optical force (LOF) acting on sub‐10 nm non‐chiral particles can be obtained using a dipole‐quadrupole (DQ) Fano resonance (FR). This DQ‐FR is excited by an asymmetric plasmonic bowtie nanoantenna array (BNA), which is based on a Au/Ge2 Sb2 Te5 /Au trilayer. The LOF behaves in a direction in which the incident light has neither a spin‐orbit coupling nor any wave propagation. Analytical theory reveals that the LOF originates from the "hotspot" established by the DQ‐FR in the asymmetric BNA. The direction of DQ‐FR induced LOF is reversibly switched with the phase transition of Ge2 Sb2 Te5, which in turn pushes the achiral nanoparticle sideways in the opposite direction. A photo thermal model is used to study the temporal variation of the temperature of the Ge2 Sb2 Te5 film to show the potential for transiting the Ge2 Sb2 Te5 phase. Particularly, the design of hybrid nanostructure integrating a ground metal mirror can excite a strong magnetic resonance, which enhances the DQ‐FR induced LOF and reduces the Brownian motion effect on the nanoparticles. Hence, our scheme leads to a rapid and stable transportation of nanoparticles with radii as small as 10 nm. Abstract : Herein, it is numerically demonstrated that the dipole‐quadrupole (DQ) Fano resonance (FR) induced lateral force exerted on the dielectric nanoparticle accomplishes a wide tuning range in the mid‐infrared regime by switching between the amorphous and crystalline states of the Ge2 Sb2 Te5 dielectric layer in the asymmetric bowtie nanoantenna array, and in turn pushes the nanoparticle sideways in the opposite direction for a given wavelength.